Analisis Pengaruh Pembangunan Daerah dan Keuangan Syariah Terhadap Kesejahteraan Masyarakat - Fakhrezi Wildan Harahap; Andrian Syaputra; Rahmad Mulia Tama Nasution; Nurhayati Harahap (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The growth of Islamic banks in terms of distribution of funds nationally is quite large. The large amount of funds that have been successfully distributed will ultimately improve human welfare. This is because one of the objectives of operating banking using sharia principles is to improve the level of community welfare. The problem in this research is how development impacts indigenous communities and how sharia finance impacts communities. using the literature study method to analyze how development impacts indigenous communities and how sharia finance impacts communities prepares local communities to increase their ability to participate in regional development and sharia finance. Through the literature method.